2015
DOI: 10.1007/s10646-015-1480-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine: fructose-6-phosphate amidotransferase in the white shrimp Litopenaeus vannamei: characterization and regulation under alkaline and cadmium stress

Abstract: Heavy metal residues and chemical contaminators considered as relevant sources of aquatic environmental pollutants have a generally immunosuppressive effect on aquatic organisms, depressing metabolic activities and immune response. Glutamine: fructose-6-phosphate aminotransferase (GFAT, EC2.6.1.16) is the first, and rate-limiting, enzyme in the hexosamine biosynthetic pathway, and is involved in the regulation of chitin biosynthesis and glycosylation of proteins. We have isolated and characterized GFAT from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…42,69,70 For instance, when Litopenaeus vannamei is exposed to alkaline pH conditions and cadmium stress, LvGFAT is strongly expressed in the liver, indicating its importance in environmental stress resistance. 71 Inhibition of GFAT expression can significantly increase the deformity and mortality rates in Nilaparvata lugens. 72 Bolognesi et al 73 reported that Sf CHSB and Sf CHI are highly expressed in the midgut epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,69,70 For instance, when Litopenaeus vannamei is exposed to alkaline pH conditions and cadmium stress, LvGFAT is strongly expressed in the liver, indicating its importance in environmental stress resistance. 71 Inhibition of GFAT expression can significantly increase the deformity and mortality rates in Nilaparvata lugens. 72 Bolognesi et al 73 reported that Sf CHSB and Sf CHI are highly expressed in the midgut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…frugiperda larvae was less than 50% (Figure A) following treatment with larvae 6a, 7b, and 7e, primarily owing to abnormal chitin metabolism. Previous studies have shown that GFAT and GNAPNA play regulatory roles in chitin biosynthesis. ,, For instance, when Litopenaeus vannamei is exposed to alkaline pH conditions and cadmium stress, LvGFAT is strongly expressed in the liver, indicating its importance in environmental stress resistance . Inhibition of GFAT expression can significantly increase the deformity and mortality rates in Nilaparvata lugens .…”
Section: Discussionmentioning
confidence: 99%
“…The GFAT controls the flux of glucose into the hexosamine pathway and is involved in the regulation of glycosylation of proteins; and the NDK protein may display multiple functions in diverse biological processes and is involved in the promotion of cancer. Transcripts coding for these proteins have been upregulated in response to several stressors, including viral infection in the white shrimp (Litopenaeus vannamei) (Liu et al, 2015(Liu et al, , 2017, which would indicate that paralarvae fed on A diet would be in poorer condition than those fed on M diet. In fact, caspase 3 that is involved in the apoptotic process was over-expressed in the A group.…”
Section: Discussionmentioning
confidence: 99%